2017
DOI: 10.1063/1.4974275
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis of dissolution-driven convection in porous media

Abstract: We study the stability of dissolution-driven convection in the presence of a capillary transition zone and hydrodynamic dispersion in a saturated anisotropic porous medium, where the solute concentration is assumed to decay via a first-order chemical reaction. While the reaction enhances stability by consuming the solute, porous media anisotropy, hydrodynamic dispersion, and capillary transition zone destabilize the diffusive boundary layer that is unstably formed in a gravitational field. We perform linear st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 65 publications
6
39
2
Order By: Relevance
“…However, the capillary transition zone allows vertical flow across the interface between the capillary transition zone and the diffusive boundary layer, affecting the onset of the natural convection. The effects of the capillary transition zone on the onset of convection have been studied by considering either a permeable upper boundary condition in a single-phase system [2][3][4][5] or a transition zone in a two-phase system [6][7][8]. These studies demonstrated that the capillary transition zone could potentially decrease the onset time of instability by threefold [5], fivefold [4], or even sixfold [6,8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the capillary transition zone allows vertical flow across the interface between the capillary transition zone and the diffusive boundary layer, affecting the onset of the natural convection. The effects of the capillary transition zone on the onset of convection have been studied by considering either a permeable upper boundary condition in a single-phase system [2][3][4][5] or a transition zone in a two-phase system [6][7][8]. These studies demonstrated that the capillary transition zone could potentially decrease the onset time of instability by threefold [5], fivefold [4], or even sixfold [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we further examined the effect of the capillary transition zone on the onset of instability and natural convection by extending the linear stability analysis (LSA) presented in [6,8] to remove three assumptions. First, we considered a three-dimensional, two-phase (gas and water), two-component (CO 2 and H 2 O) physical system with Darcy's velocities in x-, y-, and z-direction instead of using two-dimensional stream function equations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase of the density is heterogeneous in the different part of the formation. A local increase of density, coupled with the heterogeneity of the aquifer such as permeability heterogeneity [18] , will result in the instability of the gravity and prompt the onset of the viscous finger [19][20][21][22] . The viscous finger will lead to the convective mix, accelerating the process of CO2 solution in the brine and reducing the possibility of CO2 leakage.…”
Section: Figure 2 Options For Storing Co2 In Deep Underground Geologimentioning
confidence: 99%